1997
DOI: 10.1007/bf00393710
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of costs in ankle fractures treated with absorbable or metallic fixation devices

Abstract: The economic costs of ankle fractures treated operatively with self-reinforced polyglycolide acid (SR-PGA) screws, with self-reinforced poly-L-lactide acid (SR-PLLA) screws or with metallic implants was determined. All patients were divided into three groups according to the fixation material used. Open and otherwise complicated fractures were excluded. The total expense of operations in each group was taken into account. The average total cost of an ankle fracture fixed with SR-PGA screws was Pounds 3503. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 17 publications
0
15
0
3
Order By: Relevance
“…Bone mineral density (BMD) was measured after operative ankle fracture treatment with bioabsorbable SR-PLLA or metallic screws [3]. The average BMD value in the distal tibia was 18% lower after metallic screw fixation compared to the non-operated ankle as early as after 1.4 years; after SR-PLLA screw fixation the BMD value was only 6.4% lower than in the non-operated ankle after 3.9 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone mineral density (BMD) was measured after operative ankle fracture treatment with bioabsorbable SR-PLLA or metallic screws [3]. The average BMD value in the distal tibia was 18% lower after metallic screw fixation compared to the non-operated ankle as early as after 1.4 years; after SR-PLLA screw fixation the BMD value was only 6.4% lower than in the non-operated ankle after 3.9 years.…”
Section: Discussionmentioning
confidence: 99%
“…As bioabsorbable implants degrade gradually there is no need to remove the implants. Moreover, the economic impact of bioabsorbable fixation devices seems to be more favourable than that of metallic implants in the operative treatment of ankle fractures when all expenses are considered [4].…”
Section: Discussionmentioning
confidence: 99%
“…Implantate aus biologisch abbaubaren Kunststoffen wie Polydioxanon (PDS), Polylaktid (PLA) und Polyglykolid (PGA) haben bereits Eingang in die klinische Praxis gefunden [1,2,3,4,5,6,10,11,13,14,15,19,20,24,27,28,31]. Polyglykolide zeigen eine große initiale Festigkeit aber rapide Festigkeitsverluste nach der Implantation sowie eine hohe Rate an Fremdkörperreaktionen bei der klinischen Anwendung [15,18,22,32].…”
Section: Osteosynthesepins · Femurkortikalis · Festigkeitseigenschaftenunclassified
“…Revision surgery hence increases the medical costs as well as the health risks for patients. The development of absorbable orthopaedic devices aims to lower these medical expenses, and evidence has shown that total medical expenses were lower when using absorbable (polymer) orthopaedic devices compared with traditional non-absorbable metallic devices [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%